TINJAUAN YURIDIS TERHADAP PELAKU TINDAK PIDANA PEDOFILIA MENURUT UU NO 35 TAHUN 2014 TENTANG PERUBAHAN UU NO 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Agustinus Aldy Pratama; Safik Faozi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
Similarly in order children protection, country and government has responsible to provides and accessibility for children. Especially in guaranteeing optimal growth and development of the child directed as in the explanation of Law Number 23 of 2002 about Child Protection. Based on the background above, the title is taken Juridical Review of Perpetrators of Pedophilia Crimes According to Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. This research normative juridical type of research, research specifications in this research in inconcreto legal research, This research used secondary data. Data collection methods used literature study. Data presentation methods by editing, data analysis methods using qualitative descriptive analysis methods. The results of this research are that the juridical review of perpetrators of pedophilia crimes is in accordance with the applicable laws and regulations, namely according to Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, also knowing the form of protection for victims of pedophilia crimes.